(untitled) (Revista de Estudos da Linguagem, 2007)
In this article we present the first application of the theory of Languagein Act (CRESTI, 2000b) to Brazilian Portuguese. After a summaryof the theory is presented, we show how a text can be divided inutterances and how the utterance can be divided in tone units, throughthe perception of terminal and non terminal prosodic breaks. Basedon dedicated entonational profiles, we show the informational taggingof the tone units, which is motivated by prosodic, functional anddistributional criteria. We conclude by showing how the prosodicand informational frame clearly change, depending on turn size andevidence of the illocutionary principle.